Evaluation of Public Tender Law Changes in Turkey in Context of Economic Sustainability - AKYILDIZ, Nihal Arda (International Journal of Scientific Research and Management (IJSRM), 2020)
In today's economic system, the state has to make some purchases of goods and services to produce and offer the services of the public system formed by local administrations and other administrations. These purchases are the purchases that the public deems necessary through the private sector within the framework of investment programs and budget. Although annual growth and the tranches of spending items in investment programs change every year within the framework of the country's growth, purchases in the public system necessarily occur depending on these rates. Regulations and improvements on this subject; will not only affect the current levels of economic and social welfare, but will also increase the welfare levels of future generations and will support economic sustainability. The issue of public purchases regulated by law, which has become more important especially with its wide coverage in the Eleventh Development Plan, continues to contribute to economic sustainability with its value that directs the country's economy.In the study, literature reviews of public procurements, tender laws and related regulations which have a direct effect on the country's economy were conducted as method; and changes in the public procurements, tender laws and relevant legislation have been aimed to be revealed. Since the first law of 1925, in the four law amendments, some regulations have been made abiding by the main principles and the arrangements required by the country have been made. While the names of the procurement procedures change in the laws are partial, the main contents are preserved. The study examines the four procurement laws that have changed in this way; aiming to provide information on the subject and to address the forecasts that are realized with the support of the country's economy and sustainable development. Keywords: Tender law, public procurement legislation, economic sustainability, sustainable development, procurement procedures and implementing regulations